The application of soft systems methodology as a participatory education strategy in the stunting reduction program in Garut Regency - Ilahi, Yosef Hadyan Fazzar; Kania, Ikeu; Akbar, Gugun Geusan (ARKA INSTITUTE, 2025)
This study explores the application of Soft Systems Methodology (SSM) as a participatory education strategy in a stunting reduction program in Garut Regency, a region facing unequal access, limited infrastructure, and low community involvement in educational decision-making. A qualitative SSM-based approach was used. Data were collected through semi-structured interviews (45-60 minutes) and participant observation with 60 purposively selected respondents: elementary/junior high school teachers, parents/guardians, education officials, village/sub-district heads, school committee members, and representatives from businesses/NGOs drawn from three districts representing geographic variation and accessibility. Analysis with NVivo 14 used thematic coding, word clouds, and matrix coding. Four main themes emerged: (1) access and infrastructure challenges (32% of 3,456 coded references), (2) diverse stakeholder engagement (28%), (3) curriculum adaptation based on local Sundanese culture (21%), and (4) the impact of SSM on sustainable change (19%). Matrix coding showed a strong correlation between the intensity of stakeholder engagement and the perceived effectiveness of SSM-based change. These findings confirm SSM as an effective learning approach for designing contextual participatory education programs and contribute to SDG 4 on quality education for designing stunting reduction interventions.